CXCL12α/SDF‐1 from perisynaptic Schwann cells promotes regeneration of injured motor axon terminals - Samuele Negro; Francesca Lessi; Elisa Duregotti; Paolo Aretini; Marco La Ferla; Sara Franceschi; Michele Menicagli; Elisanna Bergamin; Egle Radice; Marcus Thelen; Aram Megighian; Marco Pirazzini; et al. (EMBO Molecular Medicine)
Abstract The neuromuscular junction has retained through evolution the capacity to regenerate after damage, but little is known on the inter‐cellular signals involved in its functional recovery from trauma, autoimmune attacks, or neurotoxins. We report here that CXCL12α, also abbreviated as stromal‐derived factor‐1 (SDF‐1), is produced specifically by perisynaptic Schwann cells following motor axon terminal degeneration induced by α‐latrotoxin. CXCL12α acts via binding to the neuronal CXCR4 receptor. A CXCL12α‐neutralizing antibody or a specific CXCR4 inhibitor strongly delays recovery from motor neuron degeneration in vivo. Recombinant CXCL12α in vivo accelerates neurotransmission rescue upon damage and very effectively stimulates the axon growth of spinal cord motor neurons in vitro. These findings indicate that the CXCL12α‐CXCR4 axis plays an important role in the regeneration of the neuromuscular junction after motor axon injury. The present results have important implications in the effort to find therapeutics and protocols to improve recovery of function after different forms of motor axon terminal damage.